Habitat dan Keragaman Tumbuhan Pakan bagi Tapir (Tapirus indicus), Kijang (Muntiacus muncak) dan Kukang (Nycticebus coucang) di Kawasan Gunung Tujuh, Taman Nasional Kerinci Seblat, Jambi - W. Rosa Farida; Wirdateti Wirdateti; H. Dahruddin; G. Sumaatmadja (Universitas Andalas, 2006)
Research on the habitat and the diversity of feed plants of tapir (Tapirus indicus), barking deer (Muntiacus muncak) and slow loris (Nycticebus coucang) have been conducted at Gunung Tujuh, Kerinci Seblat National Park, Jambi. Survey was carried out by visiting places where tapir, barking deer, and slow loris are usually seen and taking collecting herbarium plant specimen of those animals’feed. The habitat of tapir is in region of Gunung Tujuh forest until the altitude of 2020 m asl. The habitat of barking deer in Gunung Tujuh forest and prefers dense bushes at the edges of forest until the altitude of 1620 m asl. and the habitat of slow loris in low region of forest. This research found 38 species grouped in 25 families of forest plants as feed resources for tapir, barking deer and slow loris.